Features of Cultural Significance of Animal Science - Renata MIKHAILOVA; Vladimir SEMENOV; Anatolii TIKHONOV; Nadezhda SERGEEVA; Olga FEDOROVA; Valentina STEPANOVA; Ekaterina AGAEVA; Marina CHERNOYAROVA; Eleonora BARKOVA; Mikhail PRONIN; Andrey Evgenievich Makushev (Communications of International Proceedings, 2021)
The development of modern animal science requires an in—depth study of the problems associated with it.These problems are generated in the system of relations between man and nature. On one of its practical basis is the receipt of funds for the satisfaction of vital needs through the animal, for which a subject is oriented to actively interact with farm animals; on the other, farm animals whose quality of life needs to be improved, which raises the problem of protecting them. We are talking about the problem of interaction between man and farm animals, which is associated with cultural significance of animal science. We consider the factors of this cultural significance — nature, society, the subject. The paper develops the forms of cultural significance for man, for society: a) creating means to meet human needs through the body of an animal, which is associated with the formation of a certain level of satisfying cultural existence of man; b) development of rational thinking of a person employed in animal breeding, which subsequently leads to the development of animal science; c) ‘rooted consciousness’ of the breeder, the formation of his ‘sense of place’ and the feeling and image of ‘his place’. The paper establishes the aspects of man – farm animals relation: 1) as to a specific object; 2) as to a specific subject. The paper considers the features of these relations from antiquity to the present and for the potential future in the context of changing conditions of the external environment (society).
Keywords: Nature; Farm Animals; Specific Object; Specific Subject; Animal Science; Cultural Significance.